Local ecological knowledge as a complementary basis for the management of water resources - Sobczak, Jesse; Valduga, Alice; Restello, Rozane; Cardoso, Rafael; Hepp, Luiz Ubiratan; Siqueira, Andre (Ethnobiology and Conservation, 2013)
Public participation in the management of water resources is gradually being incorporated into environmental monitoring programs. However, effective performance depends on the applicability of the methods and on the scope of public enrollment because of the complexity of the local ecological knowledge (LEK) acquired to support the process. This study aimed to evaluate the relationship between LEK and scientific knowledge (SK), with an emphasis on water quality. Social and natural science methods were used. The study involved a conservation unit (CU) located in the Alto Uruguai region of southern Brazil and consisted of two stages: (i) interviews using a socio-environmental diagnosis of the community surrounding the CU and (ii) the collection of benthic macroinvertebrates at sampling sites located within and outside the CU. The study hypothesis that LEK could predict water quality was not confirmed (r= 0.19; p= 0.07). However, the data suggested that LEK might tend to act as an indicator of environmental quality. Although, the relationship between LEK and SK was not completely specified, the study identified several features associated with water quality. This result provided a preliminary approach to the understanding of water quality. We suggest that future studies include additional variables potentially related to water quality and that such studies also incorporate temporal perspectives. The addition of LEK to SK can, indeed, furnish a more complete understanding of the management and conservation of a natural system.